Modernization of the African Culture: The Town Crier and Gender in Patrick Naagbanton’s Writings - Njoku, Anthony (Journal of Gender and Power, 2023)
African oral tradition and literature has been relegated to the background and termed inferior because it is erroneously misconceived by the West whose written culture and civilization is presumably superior. African writers have to mobilize their intellectual energy to disprove the West by enriching their writings, culture and heritage. Again, the modern African nation especially the Nigerian nations’ state is fraught with violence and injustice and therefore remains a dangerous place for creative writers, activists and investigative journalists who fictionalize realities and engage in human rights campaigns. The town crier is a character in a traditional stage that disseminates information by going around with a beaten gong. Can we assign the role of this town crier to contemporary writers, activists and journalists? This paper made enquiry into this question by following a qualitative research approach and by studying Naagbanton’s writings, using Viktor Shklovsky’s defamiliarisation technique as well as Susan Andt’s reformist feminism. In the end, it discovered that the author has revived the African town crier culture and given it a modern outlook and the primordial town crier now has reincarnated in ace creative writers, activists and journalists who are the current advocates of information, equity and justice and who, for attesting to the truth, run great risks in the hand of state apparatus and machinery of violence like the police, the army and the State Security Services (SSS). The paper further discovered that the town crier motif in African culture now finds a new voice at the global setting in Naagbanton’s works, taking both male and female gender, and that most exponents of justice, truth and equity are masked town criers. It recommends that aspects of African ancient culture should be rehabilitated to meet new trends and modern universal standards.